2023
DOI: 10.1111/exd.14773
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid alleviates ultraviolet‐mediated skin aging via attenuation of mitochondrial and ER stress responses

Abstract: UV-B radiation is a crucial determinant of skin cells' fate. Chronic UV-B exposure induces a myriad of cellular and molecular changes that are detrimental to skin health, leading to a global response known as photodamage. 1 Photodamage refers to both premature aging and photocarcinogenesis, both giving a sequential picture of progression of skin malignancies. 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Sanchez-Campillo et al suggested that rosmarinic acid may be beneficial as functional, nutraceutical and pharmaceutical product for oral administration and dermatologic photo-protective formulations. It has been reported that rosmarinic acid exhibits the effect of anti-photodamage from UVB exposure in chronic animal model (Balb/C mice) by prevention endoplasmic reticulum stress and impairment of mitochondrial dynamics via alleviation of the oxidative stress ( Gupta et al, 2023 ). Therefore, we expected that ST ethanolic extract containing rosmarinic acid would have potential effect on UVB-induced skin photodamage.…”
Section: Discussionmentioning
confidence: 99%
“…Sanchez-Campillo et al suggested that rosmarinic acid may be beneficial as functional, nutraceutical and pharmaceutical product for oral administration and dermatologic photo-protective formulations. It has been reported that rosmarinic acid exhibits the effect of anti-photodamage from UVB exposure in chronic animal model (Balb/C mice) by prevention endoplasmic reticulum stress and impairment of mitochondrial dynamics via alleviation of the oxidative stress ( Gupta et al, 2023 ). Therefore, we expected that ST ethanolic extract containing rosmarinic acid would have potential effect on UVB-induced skin photodamage.…”
Section: Discussionmentioning
confidence: 99%
“…Gapdh was utilized as the loading control. All the data (analyzed by the ΔΔCt method) were normalized to the control gene as described previously 26 2.10. Immunocytochemistry of MITF.…”
Section: Gene Expression Analysis (Qpcr)mentioning
confidence: 99%